Uji Efek Nefroprotektor Ekstrak Etanol Kulit Manggis (Garcinia Mangostana L.) terhadap Kerusakan Histologis Sel Ginjal Tikus Putih yang Diinduksi Gentamicin - Indhira Justine Ginting; Asyrun Alkhairi Lubis; Muhammad Yunus (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
Gentamicin is an antibiotic widely used in medicine to treat serious bacterial infections, particularly urinary tract, respiratory tract, skin, and soft tissue infections. This drug belongs to the aminoglycoside class, which works by inhibiting bacterial protein synthesis, preventing bacterial survival. Despite its high efficacy, gentamicin has significant side effects, particularly on the kidneys. Long-term or high-dose use of gentamicin can cause nephrotoxicity, which is damage to kidney tissue characterized by decreased filtration function, impaired glomerular and tubular structure, and increased blood creatinine and urea levels. This occurs because gentamicin tends to accumulate in the proximal tubules of the kidneys, triggering oxidative stress and inflammation. To reduce the toxic effects of gentamicin on the kidneys, nephroprotective agents are needed. One potential natural ingredient is mangosteen rind extract (Garcinia mangostana). Mangosteen rind is known to contain active compounds such as xanthones, which have antioxidant, anti-inflammatory, and antimicrobial properties. This compound is capable of neutralizing free radicals and suppressing the inflammatory response, which is one of the causes of kidney tissue damage. This study aimed to determine the effect of mangosteen peel extract on the histological appearance of the kidneys of rats treated with gentamicin. Histological analysis was performed to observe changes in kidney structure, such as tubular cell degeneration, necrosis, or inflammatory cell infiltration. It is estimated that administering mangosteen peel extract can minimize or prevent kidney tissue damage, making it an alternative complementary therapy to gentamicin. This research also marks the first step in the development of safe and effective herbal-based phytopharmaceuticals to support kidney health.